The Importance of Forest Elephants for Vegetation Structure Modification and Its Influence on the Bird Community of a Mid-Elevation Forest on Mount Cameroon, West-Central Africa - Kamga, Solange Mekuate; Tamungang, Simon Awafor; Awa, Taku; Ewome, Francis Luma; Motombi, Francis Njie; Hořák, David; Riegert, Jan (Diversity (Basel), 2022)
Most of the tropical rainforests are subject to both anthropogenic and natural disturbances. Forest elephants (Loxodonta cyclotis) cause forest clearings within the tropics. This study was conducted at mid-elevations (1100–1700 m a.s.l.) in Mount Cameroon National Park. We assessed the difference in the structure of bird communities in the forest and areas located nearby affected by elephant activities. We used the point-count method; 22 points were established within each habitat. The vegetation was visually estimated within a 50 m radius surrounding each counting point. In total, 1603 birds from 85 species were recorded. The vegetation cover from 3 to 5 m at points with elephant activity was significantly lower compared to points without elephant activity. Bird species richness was significantly higher around points in pasture compared to points in intact forest. Habitat type and the percentage of vegetation layer from 3 to 5 m significantly impacted the bird community structure. The points in the pasture were especially characterized by the increased abundance of some open habitat species (e.g., Chubb’s Cisticola chubbi). Few studies have documented the effects of elephant activity on other species, although the effects are widely stated as important drivers of habitat diversity in tropical forests. In conclusion, disturbance caused by elephants leads to increased bird community diversity due to the increased heterogeneity of the environment, which documents the high importance of elephants as ecosystem engineers.